Comparative Efficacy of Intranasal Corticosteroids vs. Antihistamines in Allergic Rhinitis: A Randomized Biochemical-Based Study - Waqas Javaid, Muhammad Usman Khalid Amin, Saleha Safdar, Ziaullah, Ghulam Dastgir Khan, Muhammad Naeem, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Allergic rhinitis (AR) significantly impairs quality of life and presents with chronic nasalinflammation. This randomized open-label study compared intranasal corticosteroids (INCS) andoral second-generation antihistamines (AH) in 120 adult patients over 8 weeks